Knowledge Management as an Effort to Develop Learning Organizations in Islamic Educational Institutions - Ainur Rahman; Rosyidah Dzunur’aini; Ika Nur’aini (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2022)
The development of science and technology requires educational institutions to make changes to keep up with the times so that human resource productivity and quality management are needed in an Islamic educational organization. This research method is the result of literature review research. The purpose of this study is to try to describe the meaning of knowledge management and learning organization as well as knowledge management as an effort to develop a learning organization in Islamic educational institutions, where knowledge management is critical to study in the development of human resource productivity in an Islamic educational institution. The results of this literature review are an educational institution, educators, and educators need knowledge management to develop and improve quality human resources, increase the value of an organization or company and increase collaboration in an Islamic educational institution.